A human salivary protein which promotes adhesion of Streptococcus mutans serotype c strains to hydroxyapatite. - Kishimoto, E (1989)
The aim of this study was to investigate the nature of one of the factors in human submandibular-sublingual (SMSL) saliva which promotes the adhesion of Streptococcus mutans serotype c strains to hydroxyapatite (HA) surfaces. Gel filtration chromatography of SMSL saliva on Trisacryl GF2000 gave a void volume peak which contained the major fraction of adhesion-promoting activity for S. mutans JBP to HA. Maximum adhesion-promoting activity, however, eluted slightly later than the maximum 220-nm absorbance of the void volume peak. Gel filtration of the void volume material after treatment with sodium dodecyl sulfate (SDS) gave an early-eluting larger peak followed by a smaller peak with which the adhesion-promoting activity was associated. SDS-polyacrylamide gel electrophoresis (SDS-PAGE) showed the presence of relatively slowly migrating material associated with the larger inactive peak, presumably mucin, and a faster-migrating band(s) associated with the smaller active peak. SDS-PAGE indicated molecular weights in the range of 300,000 to 350,000 by extrapolation from size standards. Comparison of SMSL from five individuals showed the presence of single bands or double bands associated with adhesion-promoting activity, indicating genetic polymorphism. The active material did not resemble either secretory immunoglobulin A, based on SDS-PAGE and immunoassay, or fibronectin, based on SDS-PAGE, and also differed in molecular weight from salivary mucins and salivary constituents previously reported to promote aggregation of certain oral bacteria, but a relationship to these materials cannot be excluded. This adhesion-promoting material may play a significant role in the initial colonization of tooth surfaces by S. mutans strains.